WTEC panel on tissue engineering research : final report - McIntire, Larry V. (Academic Press, 2003)
In this publication information has been gathered on the current status and future trends in research and development in the field of tissue engineering in Europe and Japan, in comparison to U.S. activity in this field. The chapters report on critical areas that form the building blocks necessary for substantial growth of the tissue-engineering field. Site reports documenting visits to university, government, and industry laboratories in Europe and Japan are included in this volume as appendices.